2022
DOI: 10.1111/all.15445
|View full text |Cite
|
Sign up to set email alerts
|

A pathogenic integrated view explaining the different endotypes of asthma and allergic disorders

Abstract: The inflammation of allergic diseases is characterized by a complex interaction between type 2 and type 3 immune responses, explaining clinical symptoms and histopathological patterns. Airborne stimuli activate the mucosal epithelium to release a number of molecules impacting the activity of resident immune and environmental cells. Signals from the mucosal barrier, regulatory cells, and the inflamed tissue are crucial conditions able to modify innate and adaptive effector cells providing the selective homing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 319 publications
0
12
0
Order By: Relevance
“…Asthma is a chronic complicated airway disease, and presents a high prevalence throughout the world (Naumova et al, 2022). Airway inflammation in asthma can be subdivided in T2-high and T2-low subsets based on molecular mechanism (Halayko et al, 2021;Maggi et al, 2022). T2-low asthma can be severe and corticosteroid resistant, and targeted interventions for T2-low asthma have been mostly unsuccessful (Durack et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is a chronic complicated airway disease, and presents a high prevalence throughout the world (Naumova et al, 2022). Airway inflammation in asthma can be subdivided in T2-high and T2-low subsets based on molecular mechanism (Halayko et al, 2021;Maggi et al, 2022). T2-low asthma can be severe and corticosteroid resistant, and targeted interventions for T2-low asthma have been mostly unsuccessful (Durack et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing mortality and morbidity rates of asthma leads to the urgent need for new anti-asthma drug development which requires deeper understanding of the molecular mechanisms underlying asthma. Airway inflammation in asthma can be subdivided in T2-high and T2-low subsets (Woodruff et al, 2009;Bhakta et al, 2013;Halayko et al, 2021;Maggi et al, 2022). Clinical biomarkers for T2-high include IgE ≥100 IU/ml, eosinophils count ≥300/μl, and FeNO ≥30 ppb (Busse et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, the Th17 pathway may also play an essential role in the pathophysiology of allergic asthma; our results also showed that allergic asthmatic adolescents presented more significant RORC , IL17A , and TNFA mRNA expression levels compared to healthy participants [ 20 ]. Apparently, IL-17A and TNF-α may also be causing lung damage in this allergic phenotype, as obesity-related asthma does [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the immune response of allergic asthma is orchestrated mainly by Th2 lymphocytes, which release IL-4, IL-5, and IL-13; consequently, there is a specific IgE synthesis by B cells and eosinophils recruitment in the respiratory epithelium [ 32 , 33 , 34 ]. In contrast, the immune response in obesity-related asthma is mediated primarily by Th17 cells, ILC3s, and M1-type macrophages; as a result, there is an increase in TNF-α, IL1-β, IL-6, IL-17A, and IL-23 [ 3 , 4 , 5 , 6 , 7 , 8 , 32 , 33 , 34 ]. It is worth emphasising that the immunological mechanisms noticeably differ between these asthmatic phenotypes, as asthma development has different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, a comprehensive endotyping strategy for asthma in which various risk factors, specific cell types, and biomarkers provide robust personalized prognostic and therapeutic approaches is lacking. 9 For instance, the role of monocytes in asthma remains to be fully understood. It has been previously reported that monocytes accumulate in the airways of children with fatal asthma attacks.…”
Section: Introductionmentioning
confidence: 99%